2017
DOI: 10.1016/j.pnpbp.2017.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation and epigenetic modification of the prodynorphin gene in peripheral blood cells in alcoholism

Abstract: Dynorphins are critically involved in the development, maintenance and relapse of alcoholism. Alcohol-induced changes in the prodynorphin gene expression may be influenced by both gene polymorphisms and epigenetic modifications. The present study of human alcoholics aims to evaluate DNA methylation patterns in the prodynorphin gene (PDYN) promoter and to identify single nucleotide polymorphisms (SNPs) associated with alcohol dependence and with altered DNA methylation. Genomic DNA was isolated from peripheral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 53 publications
0
10
0
1
Order By: Relevance
“…Another study found decreased DNAm at repetitive DNA elements (Alu) associated with alcohol use in lymphocytes from healthy individuals (Zhu et al 2012). Candidate gene approaches in blood cells have demonstrated associations between increased DNAm and AUD at the promoters for alpha synuclein ( SNCA ), homocysteine-induced endoplasmic reticulum protein ( HERPUD1 ), serotonin transporter ( SLC6A4 ), monoamine oxidase A ( MAOA ), prodynorphin ( PDYN ), and aldehyde dehydrogenase 2 ( ALDH2 ) (Bleich et al 2006; Bonsch et al 2005; Philibert et al 2008a; Philibert et al 2008b; D’Addario et al 2017; Pathak et al 2017). More recently, genome-wide profiling of methylated regions in whole blood cells or human lymphoblast cell lines has demonstrated several significant differentially methylated regions or differentially methylated cytosines associated with high levels of alcohol drinking or dependence (Philibert et al 2012; Clark et al 2015; Liu et al 2016; Zhang et al 2013; Zhao et al 2013).…”
Section: Epigenetic Modifiersmentioning
confidence: 99%
“…Another study found decreased DNAm at repetitive DNA elements (Alu) associated with alcohol use in lymphocytes from healthy individuals (Zhu et al 2012). Candidate gene approaches in blood cells have demonstrated associations between increased DNAm and AUD at the promoters for alpha synuclein ( SNCA ), homocysteine-induced endoplasmic reticulum protein ( HERPUD1 ), serotonin transporter ( SLC6A4 ), monoamine oxidase A ( MAOA ), prodynorphin ( PDYN ), and aldehyde dehydrogenase 2 ( ALDH2 ) (Bleich et al 2006; Bonsch et al 2005; Philibert et al 2008a; Philibert et al 2008b; D’Addario et al 2017; Pathak et al 2017). More recently, genome-wide profiling of methylated regions in whole blood cells or human lymphoblast cell lines has demonstrated several significant differentially methylated regions or differentially methylated cytosines associated with high levels of alcohol drinking or dependence (Philibert et al 2012; Clark et al 2015; Liu et al 2016; Zhang et al 2013; Zhao et al 2013).…”
Section: Epigenetic Modifiersmentioning
confidence: 99%
“…Variations in the prodynorphin gene have also been associated with negative craving for alcohol (i.e., seeking alcohol for relief from a negative emotional state) and alcohol dependence (Karpyak et al., ). DNA methylation (associated with reduced gene expression) in the prodynorphin gene was increased in alcoholics relative to control subjects in cortex and blood cells (D'Addario et al., ; Taqi et al., ). Future work using animal models may be valuable in clarifying whether allelic variants of OPRK1 or epigenetic factors (e.g., differential methylation of the prodynorphin gene) significantly contribute to risk for alcohol use disorder and/or treatment responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…These results were subsequently used to test for association between the top CpGs and genotypes. A few studies searched for an association between a specific genotype and DNAm at a chosen CpG from a neighboring region [ 28 30 ]. Another study adopted a more integrative approach by utilizing all the available genetic and methylation data to search for differentially methylated CpG sites and meQTLs associated with breast cancer [ 31 ].…”
Section: Discussionmentioning
confidence: 99%